Efektivitas Penerapan Undang-Undang No. 35 Tahun 2009 Tentang Tindak Pidana Narkotika (Studi Kasus di Wilayah Kota Surakarta) - Nugroho, Zanuar Eko, Kuswardhani, S.H., M.Hum, Hartanto, S.H., M.Hum (2017)
Effectiveness constitutions is a means of comparing with an aspiration law. Impact studies, comparing reality with the ideals of the law, whichhas operational understanding clearly and specifically. The meansuring instrument is the law valid intentions clear legal regulation or a rule that a certain policy. So to speak effectively whether or not a rule of law is seen from how mucc people obey these laws and depending on its importance. If people obey the law because of the interest- abiding because of the sanctions, to be obedient because maintaining good relations, the degree obedience very low and it can be concluded that a legal rule does not effective community that. Because if society as abiding as the intrinsic value adopted, it means that a community is a already obeyed the law and these laws are very effective.